ISCHAEMIA IN THE NEONATE–CASE REPORT - Rodrigues, Roger (2018)
Introduction: Peripheral ischaemia and gangrene in a neonate is rare,with fewer than a hundred cases reported in the literature. Neonatal limb ischaemia present considerable challenges in diagnosis and management. The published literature is limited to case reports and case series and there are no large trials comparing different therapies. Objectives: The authors describe the case of a 4-day newborn transferred to the Pediatric Hospital for a gangrene of the lower limb. Results: In this case the member was not salvageable. Treatment with Heparin was performed which is usually effective in cases of neonatal limb ischaemia, but in this case the evolution was not favorable. The diagnosis was late and an amputation of the leg was performed. A multidisciplinary team of surgeons, paediatricians, occupational therapists, physiotherapists, working together provided the best support network and best treatment for this child. Conclusions: Neonatal limb ischaemia is uncommon, but can have devastating consequences on the patient. Successful management is dependent on early recognition, rapid clinical assessment and appropriate therapy. Initial supportive therapy may be appropriate with aggressive interventional treatment reserved for selective cases. Interventional treatment includes thrombolysis using a tissue plasminogen activator which can be catheter directed or systemic, and surgical thrombectomy, particularly if larger vessels such as the abdominal aorta are involved. Strategies for management are still evolving, and there is only a limited pooled experience available for review in the published literature.